2022
DOI: 10.1155/2022/3380605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TAVR Approach and Other Baseline Factors on the Incidence of Acute Kidney Injury: A Systematic Review and Meta-Analysis

Abstract: Background. Acute kidney injury (AKI) is a well-known complication following a transcatheter aortic valve replacement (TAVR) and is associated with higher morbidity and mortality. Objective. We aim to compare the risk of developing AKI after transfemoral (TF), transapical (TA), and transaortic (TAo) approaches following TAVR. Methods. We searched Medline and EMBASE databases from January 2009 to January 2021. We included studies that evaluated the risk of AKI based on different TAVR approaches. After extractin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…From the baseline of this study, we observed that the via transfemoral pathway is more used, which inherently mitigated the risk of AKI development. Alzu'bi et al [25] investigated the risk of AKI following TAVR procedures conducted via transfemoral, transapical, and transaortic approaches. Their analysis revealed that patients undergoing the transfemoral approach exhibited a significantly lower risk of AKI compared to those undergoing transapical and transaortic approaches.…”
Section: Continuedmentioning
confidence: 99%
“…From the baseline of this study, we observed that the via transfemoral pathway is more used, which inherently mitigated the risk of AKI development. Alzu'bi et al [25] investigated the risk of AKI following TAVR procedures conducted via transfemoral, transapical, and transaortic approaches. Their analysis revealed that patients undergoing the transfemoral approach exhibited a significantly lower risk of AKI compared to those undergoing transapical and transaortic approaches.…”
Section: Continuedmentioning
confidence: 99%